2019
DOI: 10.1096/fj.201901480rr
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola helminth defense molecule‐1 protects against experimental arthritis by inhibiting osteoclast formation and function without modulating the systemic immune response

Abstract: An inverse correlation between helminth infection and the autoimmune disease appears to be contributed by the anti-inflammatory factors produced by these organisms. Suppressing osteoclast function without affecting the systemic immunological response is an emerging therapeutic strategy for rheumatoid arthritis (RA). We observed that a synthetic peptide corresponding to 34 amino acids of C-terminal sequence of Fasciola helminth defense molecule-1 (C-FhHDM-1) inhibited RANKLinduced osteoclast formation and lysos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…In benign situations like infections and inflammation, the systemic immune response is essential. Recent research suggests its diagnostic utility in high-grade tumors [66][67][68]. Qi et al established the SIRI as a new inflammatory marker.…”
Section: Discussionmentioning
confidence: 99%
“…In benign situations like infections and inflammation, the systemic immune response is essential. Recent research suggests its diagnostic utility in high-grade tumors [66][67][68]. Qi et al established the SIRI as a new inflammatory marker.…”
Section: Discussionmentioning
confidence: 99%
“…After treatment, calvaria were removed and processed for RNA isolation by trizol method (30). qPCR was performed by SYBR green chemistry (Thermo Fisher Scientific, Ealtham, MA, USA) for the quantitative determination of bone morphogenetic protein 2 (BMP2), type 1 collagen (Col I), receptor activator of nuclear factor kappa-B ligand (RANKL), and osteoprotegerin (OPG) as described previously (31). cDNA was synthesized by using 2mg RNA (Cat no.…”
Section: Measurement Of Osteogenic Gene Expressionmentioning
confidence: 99%
“…ES-62, a glycoprotein secreted by the rodent filarial nematode Acanthocheilonema viteae inhibits functional OC differentiation by induction of anti-oxidant response gene expression, thereby resulting in reduction of the reactive oxygen species production that is necessary for the osteoclastogenesis (Doonan et al, 2018). Additionally, a synthetic peptide of secretory protein from Fasciola hepatica inhibited the RANKL-induced differentiation of macrophages to OCs and lysosomal acidification of differentiated OCs by inhibiting the action of vATPase which trigger bone resorption (Khan et al, 2020). In this study, we found that LPS enhanced osteoclastogenesis from RAW264.7 macrophages upon RANKL stimulation in vitro, whereas IL-4 had little effect on RANKL-induced OC formation, indicative of a greater osteoclastogenic differentiation ability of M1 macrophages compared to M2 phenotype (Figure S2).…”
Section: Treatment With Mes Suppresses the Inflammatory Responses Of ...mentioning
confidence: 99%
“…Studies in animal models have demonstrated that intentional exposure to helminths or helminth-derived products can effectively alleviate inflammatory arthritis by inducing Th2 responses or FOXP3 + T regulatory cells (Barranco, 2016;Chen et al, 2016). Recent studies have shown that helminth infections or helminth products are not only capable of suppressing arthritic inflammation but can also protect against arthritis-associated bone erosion in animal models (Doonan et al, 2018;Khan et al, 2020;Sarter et al, 2017). Although macrophages play a crucial role in osteoclastic activity, the mechanism that helminths target macrophage to inhibit bone erosion in inflammatory arthritis is not well understood.…”
Section: Introductionmentioning
confidence: 99%